Pengaruh Fasilitas dan Citra Terhadap Kepuasan Pasien di Rumah Sakit Umum Daerah dr. Zubir Mahmud Kabupaten Aceh Timur - Muhammad Mufrizal; Warjio warjio; Budi Hartono (PERSPEKTIF, 2021)
Patient satisfaction is a level of patient feeling that arises as a result of the performance of health services obtained after the patient compares it with what is expected. The patient of Zubir Mahmud Hospital complains of difficulties in getting a room for his family who will perform the operation even though he already has a BPJS Health card besides that the patient is disappointed with the handling and services of Zubir Mahmud Hospital, so that it can cause a bad image of the hospital in the eyes of the patient. This type of research is a survey explanatory with a cross sectional approach. The population in this study were all patients who had used the services of the Regional General Hospital dr. Zubir Mahmud, East Aceh Regency in 2020, as many as 43,216 patients. The research sample consisted of 100 people. The data collection technique uses the documentation method, the interview method and the questionnaire method. The data analysis technique used the chi square test and multiple logistic regression tests at the 95% confidence level. The results showed that there was a significant effect between facilities (p = 0.000) and image (p = 0.001) on patient satisfaction. Facility factor with Exp value (B) of 14.489 is the most dominant factor affecting patient satisfaction of the Regional General Hospital dr. Zubir Mahmud, East Aceh Regency To the Regional General Hospital dr. Zubir Mahmud, East Aceh Regency is expected to increase the number of specialist medical services so that it can reduce cases of patient referrals to other districts so as to create a good image in the eyes of the community.